(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article describes the relationship between medicine and linguistics, and describes such fields as medical linguistics, neurolinguistics, psycholinguistics, which were formed as a result of the integration of these two sciences. In addition, the development of medical linguistics formed in the field of medicine and linguistics is discussed, and the linguopoetic aspects of lexemes used in medical poetry are discussed.